The Role of Internal Audit in Fraud Prevention of Inspectorate at the Tanah Datar Regency - Atika Amor; Fajar Ramadhan; Elsa Fitri Amran (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
Purpose: The main problem in this research is the role of internal audit in preventing fraud in the government sector, with a case study of the Tanah Datar District Inspectorate. This research aims to analyze the role of internal audit in preventing fraud in the government sector, with a case study of the Tanah Datar Regency Inspectorate. Methodology: The type of research used by the author is field research, using a descriptive qualitative method with a case study approach. The data collection techniques used by the author are interviews and documentation. The data analysis technique used in processing the data is descriptive analysis based on the COSO 2013 internal control framework. Findings: Based on the research results, it can be concluded that the internal audit at the Tanah Datar Regency Inspectorate has played a role in preventing fraud in regional government organizations by implementing supervisory functions, providing coaching, and issuing recommendations for improvement. The role of internal audit is reflected in the implementation of the control environment, fraud risk assessment, control activities, information and communication, and monitoring of the implementation and follow-up of supervisory results, thus supporting the realization of a structured internal control system within the local government environment. Novelty: None of the previous studies have specifically examined the Tanah Datar Regency Inspectorate. Tanah Datar Regency is institutionally unique due to its strong nagari (village) governance system, which is the lowest level of government with its own financial management, adding complexity to the inspectorate's oversight objectives that is not found in other regencies in Indonesia.